Kontrol Optimal untuk Model Coffee Berry Disease dengan Vektor Pembawa Colletotrichum kahawae: Optimal Control for Coffee Berry Disease Model with Carrier Vector of C. kahawae - Rizka, Sailah Ar Rizka; Kholifia, Nadia (Prodi Matematika FMIPA Unirow Tuban, 2024)
Coffee Berry Disease (CBD) is a fungal disease of coffee caused by Colletotrichum kahawae, resulting in significant losses of both quality and quantity of the coffee produced. Optimal control is applied to CBD models where the interaction between carrier vectors and pathogenic fungi is considered. Control strategies include the use of fungicides and biocontrol agents. The optimal control problem is formulated to minimise the cost of implementing the interventions, along with the numbers of infected coffee, pathogenic fungi, and their carrier vectors. The existence of optimal control and the necessary conditions for optimality are solved using Pontryagin's Minimum Principle. The cost-effectiveness of implementing several control strategies was examined using the Incremental Cost-Effectiveness Ratio (ICER). Numerical simulations demonstrate the effectiveness of optimal control in mitigating CBD.